Finite element simulation analysis of reinforced concrete bifurcated pipe and surrounding rock. (2018) - Wen-liang, Ma; Ke-lun, Wei
Based on finite element method, the calculation model of Luojiao river hydropower station's reinforced concrete bifurcated pipe structure is established, and the finite element simulation analysis of reinforced concrete bifurcated pipe and surrounding rock is carried out. The calculation model takes into account the influence of geological conditions on the structure stress of bifurcated pipe, according to the stress characteristics of bifurcated pipe in construction and operation, 10 cases are considered. To study reliability and accuracy of calculation model, results of the finite element are compared with the classical analytical solutions, which prove the validity of the finite element model. The results show that the maximum tensile stress of bifurcated pipe is 4.648 MPa in the normal operation, and the stress value is reasonable as the design basis of reinforced concrete bifurcated pipe structure; the maximum circumferential tensile stress of bifurcated pipe's surrounding rock is from 0.2 MPa to 0.8 MPa, the tensile stress value is low, cover thickness of surrounding rock is enough, Luojiao river bifurcated pipe uses reinforced concrete structure is safe and reliable.